Peran Koperasi Kredit Indonesia Terhadap Penguatan Literasi Keuangan dan Perbaikan Perilaku Keuangan - Feri Lupiana; Aldina Esty Purwanti (Universitas Sains dan Teknologi Komputer, 2023)
Financial education has not broadly translated into better financial behavior. The increase in financial behavior is influenced by an understanding of financial literacy obtained from community participation in various financial service/institutional service sectors. This study aims to examine the effect of financial literacy on the financial behavior of Credit Union (CU) members in Indonesia in realizing the 2021-2025 SNLKI strategic direction. This exploratory study uses convenience sampling taken from CU members in Indonesia. The reason for selecting respondents is the availability of very abundant data. Data collection in this study was obtained by distributing questionnaires via e-mail to members of credit unions in Kalimantan and Java. Questionnaires were randomly sent to Credit Union members over the age of 18. Data analysis used SurveyMonkey and data processing used the Microsoft Excel program which was sent to researchers. The results of the study found a positive relationship between financial literacy and financial behavior.